Implementasi Algoritma Turbo Boyer Moore Pada Aplikasi Tarian Tradisional Berbasis Android - Sulastri Sulastri (Bulletin of Computer Science Research, 2020)
Traditional dance is a dance that is passed down from the community to its people who grow and develop in certain areas. This traditional dance has a high historical value in customs. Not only does it have high historical value in customs, traditional dances also have different meanings from one region to another. This android-based traditional dance application was created which would be useful for the community, especially teenagers, as information for them, and would save more in buying books about regional dances. With this application, it will make it easier for readers to find out the meaning of a dance in their respective areas. The moore turbo boyer algorithm is an algorithm derived from the moore boyer algorithm. Where the moore turbo boyer algorithm has the advantage of having the possibility to skip the factor of a text and the moore turbo boyer algorithm also has the advantage of allowing turbo shift.